RECLAMATION OF SIMULATED CADMIUM IONS-WASTEWATER USING SUBSURFACE FLOW CONSTRUCTED WETLANDS PLANTED WITH CANNA INDICA OR TYPHA DOMINGENSIS - Duaa. S. T; A. A. H. Faisal (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to possibility of applying three constructed wetlands units (based on the vertical subsurface flow mode-operation) for treating of simulated wastewater contained cadmium ions. Iraqi sand was the substrate used for packing of mentioned units; however, Canna indica and Typha domingensis can be planted in any two units to improve of cadmium removal while the last one remains free of vegetation. The pH, DO, temperature, and Cd values were monitored in the effluents for detention time (0.5-120 h) and metal concentration (5-40 mgl-1) to estimate the performance of units. Results proved that the removal of cadmium ions can increase significantly for longer contact time and lower Cd concentration with percentage exceeding 82% beyond 5 days. Outputs of FT-IR analysis signified the presence of several functional groups that able to improve the removal process. The values of pH, DO, temperature, TDS, and EC for treated wastewater are satisfied the requirements of irrigation water.